Live-In Dalam Mengembangkan Pendidikan Lingkungan Di Desa Bara Kecamatan Air Buaya Kabupaten Buru-Maluku - Sopamena, Nurlaila; Renggiwur, Janaba; Nukuhaly, Nur Apriyani (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
Based on the analysis of the community situation in Bara Village, the basic problems faced by the community are the low human resources and the lack of community knowledge and skills regarding environmental education and land management. The community only relies on longevity plants such as coconut and cocoa. Coconut plants are carried out every two to three times a year, while harvesting of cocoa is done every year after five years of planting. Based on the results of the activities carried out by the community in Bara village, Air Buaya, Buru district, Maluku province, it can be concluded that these activities are very useful for the local community to prepare them to become environmentally aware and work because they have adequate knowledge and skills and the results can be used as sources additional income for the community itself to meet family needs. Keywords: Devotion, Love the Environment, Fulfillment of Needs